Clinical Characteristics and Bacteriological Profile of Moraxella Keratitis. Issue 9 (September 2015) - Inoue, Hidenori; Suzuki, Takashi; Inoue, Tomoyuki; Hattori, Takaaki; Nejima, Ryohei; Todokoro, Daisuke; Hoshi, Saichi; Eguchi, Hiroshi; Miyamoto, Hitoshi; Ohashi, Yuichi
Abstract : Purpose: Moraxella species are rare causative pathogens of severe sight-threatening keratitis. The aim of this study was to analyze the clinical presentation, predisposing risk factors, in vitro antimicrobial susceptibility, and treatment associated with Moraxella keratitis. Methods: We retrospectively reviewed 30 culture-proven cases of Moraxella keratitis from multiple centers in Japan. Results: The mean age of the patients was 58.4 ± 23.4 years. The most common ocular conditions were contact lens wearing (5 patients, 16.7%) and trauma (3 patients, 10.0%). Seven patients had diabetes mellitus. Sixteen patients exhibited hypopyon in association with the corneal focus. Ring-shaped infiltration was found in 9 patients (30.0%), and irregular or amoebic-shaped infiltration was observed in 13 patients (43.3%). Eight patients (26.7%) showed small round infiltrates. All Moraxella isolates were sensitive to fluoroquinolones and aminoglycosides. All were treated with a combination ophthalmic solution containing a fluoroquinolone, tobramycin, and cefmenoxime. Although no patients developed corneal perforation, the response to treatment was slow in all cases; the mean treatment period was 41.9 days. Conclusions: In Japan, Moraxella keratitis occurs in patients with contact lens wear, trauma, and diabetes mellitus. It presents as a small, round, ring-shaped, irregularly shaped, or amoebic-shaped focus. Moraxella species exhibit good susceptibility to fluoroquinolones and aminoglycosides. Because the treatment response may be very slow, these agents should be continued for a long period of time.